Protective parents and permissive children: what qualitative interviews with parents and children can tell us about the feasibility of juvenile idiopathic arthritis trials - Frances C. Sherratt; Louise Roper; Simon R. Stones; Flora McErlane; Matthew Peak; Michael W. Beresford; Helen Foster; Athimalaipet V. Ramanan; Madeleine Rooney; Eileen Baildam; Bridget Young (BMC, 2018)
Abstract Background Patient recruitment can be very challenging in paediatric studies, especially in relatively uncommon conditions, such as juvenile idiopathic arthritis (JIA). However, involving children and young people (CYP) in the design of such trials could promise a more rapid trajectory towards making evidence-based treatments available. Studies involving CYP are advocated in the literature but we are not aware of any early stage feasibility studies that have qualitatively accessed the perspectives of parents and CYP with a long term condition to inform design and conduct of a trial. In the context of a feasibility study to inform the design of a proposed randomised controlled trial of corticosteroid induction regimen in JIA, we explored families' perspectives on the proposed trial and on JIA trials generally. Methods We analysed interviews with 27 participants (8 CYP aged 8-16 years and 19 parents) from four UK paediatric rheumatology centres. CYP had recently received corticosteroids to treat JIA. Audio-recorded interviews were transcribed and analysed thematically, drawing on the Framework Method. Results Both parents and CYP were capable of engaging with the logic of the proposed trial but pointed to challenges with its design. Treatment preferences influenced willingness to participate in the proposed trial. The preferences of older children and their parents often differed, with CYP being more willing to participate in the proposed trial than parents. Families' current treatment preferences were largely informed by past positive and negative treatment experiences. Some participants also indicated that their treatment preferences were influenced by those of their clinicians. Conclusion Previous research has typically focused on deficits in patients' understandings of trials. We found that both parents and CYP understood trial concepts and were able to identify potential flaws in the proposed trial. We propose recommendations to optimise the design of a planned corticosteroid induction regimen trial in JIA. Accessing both parents' and CYP's perspectives helps to identify and address recruitment challenges, which will ultimately optimise informed consent and future recruitment.